Additive Effect of a Combination of Artocarpus lakoocha and Glycyrrhiza glabra Extracts on Tyrosinase Inhibition in Melanoma B16 Cells - Tasanee Panichakul; Teerapat Rodboon; Prasit Suwannalert; Chanchai Tripetch; Rittipun Rungruang; Nattaporn Boohuad; Piyawan Youdee (MDPI AG, 2020)
Artocarpus lakoocha (Al) and Glycyrrhiza glabra (Gg) extracts have been reported to show tyrosinase inhibitory activity and melanin pigment reduction. This is the first study to assess the combination of Al and Gg extracts in enhancing inhibition of tyrosinase and reduction of melanin pigments. Al and Gg extracted by maceration in 70% and 95% ethanol were analyzed for oxyresveratrol and glabridin using Ultra High Performance Liquid Chromatography. Extracts of Al and Gg singly and combinations of Al95 and Gg95 were tested for cytotoxicity, tyrosinase inhibitory activity, and reduction of melanin pigments in melanoma B16 cells. Al95 had higher antioxidant, tyrosinase inhibitory activity and reduced more melanin pigments in B16 cells compared to Al70, and exhibited higher levels of oxyresveratrol. Gg95 inhibited oxidative stress and mushroom tyrosinase better than Gg70, and exhibited higher levels of glabridin. Combinations of Al95 and Gg95 at various ratios (concentration of 0.1 mg/mL) were not cytotoxic to B16 cells. Interestingly, Al95 and Gg95 combined at a ratio 9:1 reduced melanin pigment up to 53% in B16 cells. This combination of Al95 and Gg95 extracts exhibited the additive effect of reducing melanin pigments by suppressing the expression of microphthalmia-associated transcription factor (MITF), tyrosinase (TYR) and tyrosinase-related protein-2 (TRP-2) in B16 cells. The combination of Al and Gg extracts could be developed as skin care products for hyperpigmentation treatment.